Operator State in a Workplace Simulation Modulates Eye-Blink Related EEG Activity - Emad Alyan; Edmund Wascher; Stefan Arnau; Ruth Kaesemann; Julian Elias Reiser (IEEE, 2023)
Evaluating and understanding the cognitive demands of natural activities has been difficult using neurocognitive approaches like mobile EEG. While task-unrelated stimuli are commonly added to a workplace simulation to estimate event-related cognitive processes, using eyeblink activity poses an alternative as it is inherent to human behavior. This study aimed to investigate the eye blink event-related EEG activity of fourteen subjects while working in a power-plant operator simulation - actively operating (active condition) or observing (passive condition) a real-world steam engine. The changes in event-related potentials, event-related spectral perturbations, and functional connectivity under both conditions were analyzed. Our results indicated several cognitive changes in relation to task manipulation. Posterior N1 and P3 amplitudes revealed alterations associated with task complexity, with increased N1 and P3 amplitudes for the active condition, indicating greater cognitive effort than the passive condition. Increased frontal theta power and suppressed parietal alpha power were observed during the active condition reflecting high cognitive engagement. Additionally, higher theta connectivity was seen in fronto-parieto-centro-temporo-occipital regions as task demands increased, showing increased communication between brain regions. All of these results suggest using eye blink-related EEG activity to acquire a comprehensive understanding of neuro-cognitive processing while working in realistic environments.